1992
DOI: 10.1093/oxfordjournals.jbchem.a123896
|View full text |Cite
|
Sign up to set email alerts
|

Expression in Escherichia coli and a Functional Study of a β-Troponin T 25 kDa Fragment of Rabbit Skeletal Muscle

Abstract: A 25 kDa fragment of beta-type troponin T (beta-TnT) was expressed in Escherichia coli, and its function as a component of the regulatory system for actomyosin ATPase was compared with that of the authentic counterpart, the full length alpha-TnT. The expressed species, designated as beta-TnT(N'-208), consists of 208 residues. It lacks the entire variable region at the amino-terminus and, near the carboxyl-terminus, a segment of 14 residues is changed from the alpha-type to the beta-type sequence. Functional te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 0 publications
1
17
0
Order By: Relevance
“…Previous results suggested that the first 45 residues of skeletal TnT are not essential for anchoring the Tn complex to the thin filament and do not play a crucial role in the cooperative response of actomyosin ATPase to Ca 2ϩ . Others have also shown (20,21) that removal of the N-terminal region of TnT does not affect the Ca 2ϩ sensitivity of actomyosin ATPase activity. However, we now know that TnT is more complex than previously thought, and changes in the N-terminal region have recently been shown to affect the structure of the C-terminal region of TnT (22, 23).…”
Section: Discussionmentioning
confidence: 97%
“…Previous results suggested that the first 45 residues of skeletal TnT are not essential for anchoring the Tn complex to the thin filament and do not play a crucial role in the cooperative response of actomyosin ATPase to Ca 2ϩ . Others have also shown (20,21) that removal of the N-terminal region of TnT does not affect the Ca 2ϩ sensitivity of actomyosin ATPase activity. However, we now know that TnT is more complex than previously thought, and changes in the N-terminal region have recently been shown to affect the structure of the C-terminal region of TnT (22, 23).…”
Section: Discussionmentioning
confidence: 97%
“…Deletion of rabbit residues 1-69 has at most a twofold effect on troponin-tropomyosin binding (14), troponin-induced tropomyosin-actin binding (12)(13)(14), and the cooperativity of thin filament assembly (12, 13). Fujita et al (15), reported normal function for a truncated form of rabbit skeletal muscle TnT that was missing residues 1-58, and includes the amino acid corresponding to Ile79 in human cardiac TnT. These previous studies are consistent with the present results, in which the Ile to Asn mutation at this site has no effect on troponin-tropomyosin binding, troponin-induced tropomyosin-actin binding, Ca 2ϩ activation of the myosin-thin filament ATPase rate, the degree of cooperativity and apparent Ca 2ϩ affinity for this activation, or cooperative myosin S-1 binding to the thin filament.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous structure-function studies of TnT have been reported, providing valuable characterization of the properties of TnT fragments and regions (see reviews in 9-11), but the functions of individual residues have not been investigated. Furthermore, two of the eight reported HCM-associated TnT mutations are within an NH 2 -terminal region that can be deleted with little loss of troponin function (12)(13)(14)(15). To address how one of these TnT mutations, Ile79Asn, causes HCM, this report characterizes the functional properties of the homologous mutation in recombinant rat cardiac TnT.…”
Section: Introductionmentioning
confidence: 99%
“…The aberrant splicing occurs in the modulatory NH 2 -terminal variable region of TnT (Fig. 3) and the alterations do not destroy the core structure (44,45) and basic activity (13) of TnT. In an isolated system such as the reconstituted myofilaments, the exclusion of exon 8 from turkey cTnT even produced higher Ca 2ϩ sensitivity in comparison with the wild type control (13).…”
Section: The Correlation Of Aberrant Ctnt Splicing With Dilatedmentioning
confidence: 98%
“…The primary structural maps of the embryonic (the asterisk indicates that the embryonic turkey cTnT map was predicted using the adult turkey cTnT sequence plus the chicken embryonic exon 5 segment, assuming the turkey exon 5 segment is identical), and adult turkey cTnT isoforms and the low molecular weight variants are also shown. The previously characterized TnT fragments T1, T2, CB3 (8) and 26-kDa (44,45) are outlined at the top of the figure to demonstrate the location of the alternatively spliced exons to the NH 2 -terminal variable region. b Calculated using the adult sequences plus the chicken embryonic exon 5 segment, assuming the turkey exon 5 segment is identical to the chicken counterpart.…”
Section: Figmentioning
confidence: 99%